Authority and Community: Reflections on Archaeological Practice at Heslington East, York. (October 2013) - Neal, Cath; Roskams, Steve
Abstract : This paper describes the successes and limitations of our community work during archaeological investigations at Heslington East in York, and draws out some of the wider lessons of this engagement. The successes involved wider participation in the archaeological process by a number of different groups, including often marginalized ones such as homeless people. It not only generated greater understanding of the historical depth of their locality, but delivered important wider skill sets in problem-solving approaches and team working. However, it also showed the conflicts that can develop in such contexts, which relate, in our case, to the fact that the university was institutionally committed to local engagement but was also the (often unwelcome) developer of a green space already used by that community for its own purposes. More generally, tensions result from a government strategy of emphasizing citizenship and localism to tackle the current eco- nomic recession, participation in which can result in tokenism rather than real empowerment of local communities. We conclude that archaeology, as socially-embedded practice, must recognize these deeper contexts and, hopefully, do more to transcend their limitations if 'community archaeology' is to deliver fully on its promises.